Toxoplasma gondii serine hydrolases regulate parasite lipid mobilization during growth and replication within the host. Issue 10 (21st October 2021) - Onguka, Ouma; Babin, Brett M.; Lakemeyer, Markus; Foe, Ian T.; Amara, Neri; Terrell, Stephanie M.; Lum, Kenneth M.; Cieplak, Piotr; Niphakis, Micah J.; Long, Jonathan Z.; Bogyo, Matthew
Summary: The intracellular protozoan parasite Toxoplasma gondii must scavenge cholesterol and other lipids from the host to facilitate intracellular growth and replication. Enzymes responsible for neutral lipid synthesis have been identified but there is no evidence for enzymes that catalyze lipolysis of cholesterol esters and esterified lipids. Here, we characterize several T. gondii serine hydrolases with esterase and thioesterase activities that were previously thought to be depalmitoylating enzymes. We find they do not cleave palmitoyl thiol esters but rather hydrolyze short-chain lipid esters. Deletion of one of the hydrolases results in alterations in levels of multiple lipids species. We also identify small-molecule inhibitors of these hydrolases and show that treatment of parasites results in phenotypic defects reminiscent of parasites exposed to excess cholesterol or oleic acid. Together, these data characterize enzymes necessary for processing lipids critical for infection and highlight the potential for targeting parasite hydrolases for therapeutic applications. Highlights: T. gondii serine hydrolases with similar catalytic folds prefer different substrates T. gondii ASH proteins are lipid-metabolizing enzymes T. gondii lipid metabolism pathways use enzymes that are viable therapeutic targets Abstract : The intracellular parasite Toxoplasma gondii relies on lipid scavenging and processing to infect its mammalian hosts. In this study, Onguka et al. characterize a set of enzymes important for lipid metabolism and identify small-molecule inhibitors that perturb lipid regulation in the parasite.